Kingdom of the Golden Dragon - Allende, Isabel (Harper Trophy, 2005)
Sixteen-year-old Alexander Cold accompanies his grandmother, a writer for a geography magazine, to the remote Forbidden Kingdom in the Himalayas to help locate a sacred statue of a golden dragon before it is stolen by a greedy outsider.